The combination of macleaya extract and glucose oxidase improves the growth performance, antioxidant capacity, immune function and cecal microbiota of piglets - Chen, Xing; Zhang, Fan; Li, Huirong; Liu, Jie; Jiang, Yanping; Ren, Furong; Huang, Libo; Yuan, Xuejun; Li, Yang; Yang, Weiren; Yang, Chongwu; Li, Shuang; et al. (Frontiers in Veterinary Science, 2023)
Abstract: This study aims to investigate the effects of macleaya extract and glucose oxidase combination (MGO) on growth performance, antioxidant capacity, immune function and cecal microbiota in piglets. A total of 120 healthy 28-day-old weaned piglets were randomly divided into two treatments of six replicates. Piglets were either received a basal diet or a basal diet supplemented with 250 mg/kg MGO (2 g/kg sanguinarine, 1 g/kg chelerythrine, and 1×106 U/kg glucose oxidase). The results showed that MGO supplementation increased average daily gain (ADG) and decreased feed:gain ratio (F/G) (P < 0.05). MGO increased serum superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) activity, and immunoglobulin G (IgG) content (P< 0.05), but decreased malondialdehyde (MDA) and interleukin 1β (IL-1β) content (P< 0.05). The jejunal mRNA expression of nuclear factor erythroid 2-related factor 2 (Nrf2), glutathione peroxidase 1 (GPX1), and heme oxygenase 1 (HO-1) were increased in MGO group (P< 0.05), while that of kelch like ECH associated protein 1 (Keap1) was decreased (P< 0.05). In addition, the Firmicutes was significantly increased at phylum levels in MGO group (P< 0.05). In conclusin, 250 mg/kg MGO improved growth and development, and regulated intestinal flora of piglets, which provided a theoretical basis for MGO as an alternative additive for antibiotics.